Myeloid sarcoma – a case report - Rup, Elżbieta; Wielowieyska-Szybińska, Dorota; Sułowicz, Joanna; Sacha, Tomasz; Wojas-Pelc, Anna; Skotnicki, Aleksander (Dermatology Review/Przegląd Dermatologiczny, 2009)
Introduction: Myeloid sarcoma (MS, other names: extramedullary myeloid tumour, sarcoma granulocyticum, chloroma) is a rare extramedullary manifestation of acute myeloid leukaemia, myelodysplastic syndrome or blast crisis in chronic myeloproliferative disorder. It may present before, concurrent with or after the bone marrow involvement. The infiltrate of immature granulocytes, or less often monocytes, erythrocytes or megakaryocytes, can localize in each organ. In about 50% of cases the lesions are numerous. Objective: Presentation of a case of myeloid sarcoma diagnosed incorrectly at the beginning of the disease as histiocytosis. Case report: We present a case of a 68-year old patient with a 3-year history of disseminated tumours that resolved spontaneously. During the patient’s first stay in the Dermatology Department histiocytosis was diagnosed. After about two years the patient was admitted again to the hospital with a massive eruption of skin tumours that lasted for 3 weeks. During the second stay, acute myeloid leukaemia, AML M5, was diagnosed based on the results of histopathological examination of the skin lesions, trephine biopsies and laboratory and imaging examination. After the diagnosis was confirmed the patient was transferred to the Haematology Department where the therapy was introduced. After about two weeks of treatment the patient’s condition worsened dramatically. The patient died due to cardiopulmonary failure. Conclusions: Myeloid sarcoma constitutes a serious diagnostic and clinical problem. In patients who present with MS and no previous history of myeloproliferative disorder the neoplasm is often misdiagnosed as high-grade non-Hodgkin lymphoma or, in cases of monocyte infiltrate, as histiocytosis. The early and correct diagnosis of MS is important for adequate therapy.